PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING (PENGAJARAN TERBALIK) UNTUK MENCAPAI KETUNTASAN BELAJAR - Tyas Fajar Afandini, ; Mahmudah, (Pendidikan Ekonomi, 2013)
The research was done at X-8 class of SMAN 2 Mojokerto. The purpose of this study is to find out the application of the Reciprocal Teaching learning model on Micro and Macro economics to achieve the students comprehensiveness of X-8 class SMA Negeri 2 Mojokerto. The data analysis showed that the learning model of Reciprocal Teaching on the subject of Micro and Macro economics class X-8 SMA Negeri 2 Mojokerto to achieve the students learning comprehension in the second round is 96.97%. It can be seen from the teacher management in managing the learning model of Reciprocal Teaching is increased in every meeting and get better. While the activities of students included in the category of active students. Student opinion on the implementation of teaching Reciprocal Teaching (Teaching reversed) is very positive.